Big Data Literature-based Bibliometric Mapping Analysis for Competences Adaptable to Industry 4.0 and 5.0: Implications for Career Orientation - Chai Ching Tan (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Abstract. This study recognizes the presence of a competence-based foundation in the career orientations of both graduate students and professionals. The career orientations of graduating students and professionals, encompassing their interests and objectives, are strongly influenced by their competencies. Competence is an essential foundation for making career choices and aligns with the firm-based competitive advantage that relies on competence (e.g., core competence and dynamic capability). Fundamentally, competence is also a structure of “career orientation” that delivers unique functions of a person or an organization, manifesting VRINO properties of differentiation (e.g., valuable, rare, inimitable, non-substitutable, and organized). Graduating students and professionals build know-why competencies (that relate to career motivation, personal meaning and identification, know-how competencies (functioning strengths that contribute to a firm’s repertoire of overall capabilities), and know-whom competencies, including communication capability. The concept of competence in career orientation is often overlooked, and only a select few deeply understand how competencies should be integrated with other aspects of career orientation. This study examines the typological characteristics of career orientation and its anchors, addressing the need for more knowledge in the current literature. Industry 4.0 and 5.0 exemplify the competencies that graduating students and professionals should possess. These industries and societies utilize intelligent cyberphysical interactions to impact various aspects such as lifestyles, product development, process controls, and industry advancement. This study utilizes the bibliometric analysis method within the limitations of research papers. It applies the Sciencedirect.com databases and focuses on the keywords “Industry 4.0 and Industry 5.0” to identify the competence clusters, essentially a thematic analysis of the interrelationships of a cluster of themes that explain the competence profile for Industry 4.0 and Industry 5.0. Six competence profiles are identified using the bibliometric method: (1) key driver cluster represented by the cyber-physical system, (2) intelligence infrastructure and intelligent factory, (3) intelligence system and resilience, (4) sustainable development goals, (5) supply chain management, stakeholders, sustainable economy, big data analytics, and digital technology, and (6) intelligent businesses. Three typological dimensions of career orientation are proposed: instrumentality (selforganization continuum), value (stability-flexibility continuum), and competence superimposition, which includes core competence in the stability segment and dynamic capability in the flexibility segment. In the context of I4 and I5, it is suggested that graduating students and professionals build a global mindset and technological competence to support globally competent organizations and their businesses.

Резюме. Це дослідження визнає наявність компетентнісної основи в кар’єрних орієнтаціях як аспірантів, так і фахівців. Кар'єрні орієнтації випускників і спеціалістів, що охоплюють їхні інтереси та цілі, сильно залежать від їхніх компетенцій. Компетентність є важливою основою для вибору кар’єри та узгоджується з конкурентною перевагою фірми, яка ґрунтується на компетентності (наприклад, основна компетенція та динамічні можливості). По суті, компетентність також є структурою «орієнтації на кар’єру», яка забезпечує унікальні функції особи чи організації, демонструючи властивості VRINO диференціації (наприклад, цінність, рідкість, неповторність, незамінність та організованість). Випускники та професіонали розвивають компетенції «знати, чому» (що стосуються кар’єрної мотивації, особистого значення та ідентифікації), компетенції «ноу-хау» (функціональні сильні сторони, які сприяють репертуару загальних можливостей фірми) та компетенції «знати кого», включаючи здатність до спілкування. Концепція компетентності в професійній орієнтації часто ігнорується, і лише деякі вибрані глибоко розуміють, як компетенції повинні бути інтегровані з іншими аспектами кар’єрної орієнтації. У цьому дослідженні розглядаються типологічні характеристики професійної орієнтації та її опори, звертаючись до потреби в більшій кількості знань у поточній літературі. Індустрія 4.0 і 5.0 є прикладом компетенцій, якими повинні володіти випускники та професіонали. Ці індустрії та суспільства використовують інтелектуальну кіберфізичну взаємодію, щоб впливати на різні аспекти, такі як спосіб життя, розробка продуктів, управління процесами та розвиток галузі. У цьому дослідженні використовується метод бібліометричного аналізу в рамках обмежень наукових статей. Він використовує бази даних Sciencedirect.com і зосереджується на ключових словах «Індустрія 4.0 і Індустрія 5.0» для визначення кластерів компетенцій, по суті тематичний аналіз взаємозв’язків кластера тем, які пояснюють профіль компетенцій для Індустрії 4.0 і Індустрії 5.0. За допомогою бібліометричного методу визначено шість профілів компетенції: (1) ключовий кластер драйверів, представлений кіберфізичною системою, (2) інтелектуальна інфраструктура та інтелектуальна фабрика, (3) інтелектуальна система та стійкість, (4) цілі сталого розвитку, (5) управління ланцюгом поставок, зацікавлені сторони, стійка економіка, аналітика великих даних і цифрові технології, а також (6) інтелектуальний бізнес. Запропоновано три типологічні виміри кар’єрної орієнтації: інструментальність (континуум самоорганізації), цінність (континуум стабільності та гнучкості) і накладання компетенцій, що включає основну компетенцію в сегменті стабільності та динамічну здатність у сегменті гнучкості. У контексті I4 та I5 пропонується, щоб випускники та професіонали розвивали глобальне мислення та технологічну компетентність для підтримки компетентних у глобальному плані організацій та їхнього бізнесу.

Ez a tanulmány elismeri a kompetenciakeret jelenlétét mind a végzős hallgatók, mind a szakemberek pályaorientációjában. A végzettek és a szakemberek érdeklődési körükre és céljaikra kiterjedő pályaorientációja erősen függ kompetenciáiktól. A kompetencia fontos alapja a pályaválasztásnak, és összhangban van a cég kompetencia alapú versenyelőnyével (pl. alapkompetencia és dinamikus képességek). Lényegében a kompetencia egy „pályaorientációs” konstrukció is, amely egyedi funkciókat biztosít az egyén vagy szervezet számára a VRINO differeciálás (pl. érték, ritkaság, egyediség, pótolhatatlanság és szervezettség) bemutatásához. A végzősök és a szakemberek know-whekompetenciákat fejlesztenek (a karriermotivációval, a személyes jelentéssel és azonosítással kapcsolatban), a know-how-kompetenciákat (funkcionális erősségek, amelyek hozzájárulnak a cég általános képességrepertoárjához) és know-who-kompetenciákat, beleértve a kommunikációs képességet is. A pályaválasztási tanácsadási kompetenciákról gyakran figyelmen kívül hagyják és csak néhány kiválasztott ismeri mélyen azt, hogy a kompetenciákat hogyan kell integrálni a pályaválasztási tanácsadás más aspektusaiba. Ez a tanulmány a pályaválasztási tanácsadás tipológiai jellemzőit és támogatásait vizsgálja, és foglalkozik a több tudás szükségességével. Az Ipar 4.0 és 5.0 példák azokra a kompetenciákra irányulnak, amelyekkel a diplomásoknak és a szakembereknek rendelkezniük kell. Ezek az iparágak és társadalmak intelligens cyber-fizikai interakciókat használnak különböző szempontok befolyásolására, például az életmódra, a termékfejlesztésre, a folyamatmenedzsmentre és az iparág fejlődésére. A kutatás a bibliometriai elemzés módszerét alkalmazza a tudományos cikkek keretein belül. A Sciencedirect.com adatbázisait használja, és az "Industry 4.0 és Industry 5.0" kulcsszavakra összpontosít a kompetenciaklaszterek azonosítására, lényegében az Industry 4.0 és az Industry 5.0 kompetenciaprofilját magyarázó témakörök egymás közötti összefüggéseinek tematikus elemzésére reflektál. A bibliometrikus módszerrel hat kompetenciaprofil került azonosításra: (1) kulcsfontosságú hajtóerő klaszter, amelyet cyberfizikai rendszer képvisel, (2) intelligens infrastruktúra és intelligens gyár, (3) intelligens rendszer és fenntarthatóság, (4) fenntartható fejlődési célok, (5) ellátási láncmenedzsment, érdekelt felek, fenntartható gazdaság, nagy adatelemzés és digitális technológiák, valamint (6) intelligens üzlet. A pályaorientáció három tipológiai dimenzióját javasoljuk: instrumentalitás (az önszerveződés folytonossága), érték (a stabilitás és rugalmasság kontinuuma) és a kompetenciák átfedéséve, amely magában foglalja az alapkompetenciát a stabilitás szegmensében és a dinamikus képességet a rugalmasság szegmensében. Az I4 és I5 összefüggésében azt javasoljuk, hogy a diplomások és a szakemberek globális gondolkodásmódot és technológiai kompetenciát fejlesszenek a globálisan kompetens szervezetek és vállalkozásaik támogatása érdekében.
Az Ipar 4.0-hoz és 5.0-hoz adaptált kompetenciák bibliometrikus feltérképezése a Big Data szakirodalom alapján: a pályaorientációra gyakorolt hatás
Бібліометричний картографічний аналіз компетенцій, адаптованих до промисловості 4.0 та 5.0 на основі літератури про великі дані: наслідки для кар’єрної орієнтації
https://aab-economics.kmf.uz.ua/aabe/issue/view/4
Keywords: Career orientation; Industry 4.0; Industry 5.0; Global Career Orientation; Bibliometric method; competences; instrumentality as career success; value orientation